Avaliação da eficácia e tolerabilidade do picossulfato de sódio no preparo mecânico do cólon quando comparado à solução de manitol a 10% - Pereira, Gabriel Carvalho Barreto (2018)
Colonoscopy is considered the gold-standard investigation method for various intestinal conditions. Adequate colonic preparation is directly related to the quality of the exam, allowing higher rates of adenoma detection and cecum intubation, two of the most important quality indicators of the exam. Given this, the purpose of this study was to evaluate sodium picosulfate’s cleansing quality and the main symptoms when compared to a 10% mannitol solution. The sample consisted of 39 patients from Hospital Universitario de Sergipe, with indications for the exam, that were split into two groups. Two forms were filled with bowel cleanliness information, according to the Boston Bowel Preparation Scale, and the main symptoms/adverse effects of each subject. The data obtained were statistically analyzed through Microsoft Excel 2017 and SPSS version 22.0. There was a predominance of female patients (74.36%), being the most frequent indication colorectal cancer screening (53.85%) and the mean age found was 55 years. Although we got better grades with sodium picosulfate’s in our study, there was no statistically significant difference in the quality of the preparation (p = 0.24) and the symptoms/adverse effects found were very similar. The data obtained by this study showed that the two preparations had very similar efficacy and conferred advantage to sodium picosulfate since it is cheaper and does not require the ingestion of lactulose. Further studies are needed to evaluate this trend, since there are few who directly compare these two preparations.